Day/night melatonin content in cerebral palsy - Santos, Janaina S. [UNESP] (2018)
Changes in the sleep-wake cycle are frequent and may impair quality of life in individuals with cerebral palsy (CP). To investigate if a lack of a day/night variation of melatonin content could be related with sleep disorders (SD), the SD were evaluated with a Sleep Questionnaire and the melatonin content using ELISA in 33 individuals with CP and 24 controls. The indicative of SD were present in 47% of CP group, and the most frequent was the indicative of sleep breathing disorder. The CP group showed higher diurnal and lower nocturnal melatonin content than controls. Individuals with CP that had indicative of SD showed lower nocturnal content of melatonin than those without SD. These results showed that the lack of the day/night variation of melatonin was related to SD in individuals with CP.